ANALISIS PRAGMATIK TERHADAP BENTUK EKSPRESI PENERIMAAN DALAM DIALOG ANTARSANTRI DI PESANTREN - Mukhamad Miftakhudin Wildani; Farida Yufarlina Rosita; Berlian Pancarrani (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study analyzes the forms of expressions of acceptance in dialogues between students in Islamic boarding schools from a pragmatic perspective. This study aims to identify various expressions of acceptance used by students in daily interactions and to understand how the social and cultural context of Islamic boarding schools influences the use of these expressions. Using a qualitative approach, data were collected through observation and recording of conversations that occurred in the Islamic boarding school environment. The results of the study indicate that expressions of acceptance can be manifested through various forms, including direct speech such as "iyo" or "matur nuwun," acceptance with choice, and nonverbal expressions such as nodding and smiling. In addition, the principles of politeness and cooperation in student communication are evident in the use of acceptance strategies that consider social norms and hierarchies in Islamic boarding schools. These findings complement the study of pragmatics in the context of communication based on Islamic values ​​and show that interaction patterns in Islamic boarding schools reflect a balance between compliance with norms and curiosity in communication.